2009
DOI: 10.1007/s12192-008-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific regulation and expression of heat shock proteins in type 2 diabetic monkeys

Abstract: The chaperone protein heat shock protein (HSP) 70 has been shown to protect against obesity-associated insulin resistance. Induction of HSPs is thus considered an exciting therapeutic strategy for diabetes (DM). The aims of this study were to (1) determine HSP levels in plasma, hepatic, and pancreatic tissues of type 2 DM primates and (2) assess the relationship between chaperone proteins of the HSP family and cellular protection. We collected plasma from 24 type 2 DM and 25 normoglycemic control (CTL) cynomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 48 publications
6
47
1
Order By: Relevance
“…Similarly, hsp60 and hsp70 were found to be induced in lymphocytes of patients suffering from type-2 diabetic nephropathy compared to controls (Calabrese et al 2007). In contrast, other studies have reported reduced systemic hsp70 expression in association with elevated glucose levels in both humans (Bruce et al 2003;Chung et al 2008) and non-human primates (Kavanagh et al 2009). This apparent discrepancy remains to be resolved.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, hsp60 and hsp70 were found to be induced in lymphocytes of patients suffering from type-2 diabetic nephropathy compared to controls (Calabrese et al 2007). In contrast, other studies have reported reduced systemic hsp70 expression in association with elevated glucose levels in both humans (Bruce et al 2003;Chung et al 2008) and non-human primates (Kavanagh et al 2009). This apparent discrepancy remains to be resolved.…”
Section: Discussionmentioning
confidence: 84%
“…Elevated glucose levels are highly associated with reduced systemic hsp70 expression in both humans (Chung et al 2008) and non-human primates (Kavanagh et al 2009). A possible mechanism is suggested by the observation that the ingestion of glucose resulted in a decreased ability to induce hsp70 (Febbraio et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…26) In addition, the levels of Hsp70 in muscle are associated with patients with insulin resistance and their first-degree relatives. 27,28) Hence, we suppose that our findings contribute to understanding of the mechanisms of insulin resistance through tuberin degradation and hamartin-Hsp70 functions. This process leads to tuberin degradation, and hamartin-Hsp70 interaction has a further unknown role (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, HSPs may offer mitochondrial protection by preventing damage to oxidation processes (Gupte et al 2008). Intriguingly, people with an inherited reduced capacity to synthesise HSPs, as well as ageing populations, have an increased risk of developing insulin resistance (McCarty 2006;Kavanagh et al 2009). Chung et al (2008) showed the expression of HSP70, but not HSP90, protein in human skeletal muscle to be markedly reduced in insulin-resistant populations, and in the skeletal muscle of type 2 diabetic humans, HSP70 expression was decreased.…”
Section: Heat Shock Proteins and Thermo-tolerancementioning
confidence: 99%